Variables associated with perceived physical and mental health in university students from Lima - Chau, Cecilia (2017)
This investigation aims to analyze the association between the perceived physical and mental health and the sociodemographic, academic and psychological variables in a group of 520 students from a private university of Lima. For this purpose, the Short Form- 36 Health Survey (SF-36), the General Self-Efficacy Scale (GSE), the Perceived Stress Scale (PSS) and the Coping Estimation Inventory (COPE 60) were used. The results show that men obtained higher scores in the dimensions of physical health compared to women. Students who had less academic difficulties obtained higher scores in the dimensions of mental health. Finally, the perceived stress exhibited stronger correlations with the dimensions of perceived physical and mental health. It is expected that these results contribute to the development of programs focused on health prevention and promotion of university students. DOI: https://doi.org/10.24265/liberabit.2017.v23n1.06